Draft Annual Plan 1976-77 Government of Maharashtra - Planning Commission (Planning Commission, 1976)
In formulating the Annual Plan for the year 1976-77 the Planning Commission had issued certain guidelines to the State Governments. These guidelines inter-alia require the State Governments to keep in mind the following factors:- the objectives of the economic programme recently announced by the Prime Minister should be kept in view; the development policy should be designed to accelerate the tempo of activities in the core sector of the economy viz. agriculture, irrigation and power.
Government of Maharashtra, Planning Department